Análise molecular e fenotípica de eventos elite de Citrus sinensis geneticamente modificado em condições de campo - Tricai, Flávia Rocha (Universidade Federal de São Carlos, 2022)
Brazil stands out worldwide as the largest orange producer. The sector has faced challenges related to phytosanitary problems and among these problems are bacterial diseases, such as citrus variegated chlorosis (CVC), citrus canker and huanglongbing (HLB). Biotechnology has sought tools aimed at plant resistance to pathogens and plant transformation has been shown to be an effective strategy. This study aimed to evaluate sweet orange plants overexpressing the MqsR toxin and the rpfF gene, regarding transgene stability, agronomic development and resistance to CVC, citrus canker and HLB. The experiment was carried out with plants of the Pineapple variety and the Hamlin variety overexpressing the rpfF gene (Pi-rpfF and H-rpfF) and Pineapple overexpressing the MqsR (Pi-MqsR), installed at the Centro de Citricultura “Sylvio Moreira” (IAC) in municipality of Cordeiropolis, SP. These plants were evaluated for chlorophyll content, development (plant height and canopy volume), resistance to CVC, citrus canker and HLB and fruit quality, always compared to non-transgenic plants (WT), performing Student's t tests at 5% significance. Only one plant from the Pi-rpfF event did not have the stable transgene. The overexpression of the genes did not change the chlorophyll content of the plants, that is, the chlorophyll was equivalent between transgenic plants and WT plants. Regarding development, H-rpfF and Pi-MqsR had lower plant height and canopy volume than WT, while PirpfF was equivalent in both traits. No symptoms of CVC and citrus canker were found in the analyzed plants. Regarding HLB symptoms, the PirpfF event showed more resistance than non-transgenic plants. The fruits from the plants under study were analyzed for mass, soluble solids, juice yield and acidity. In this analysis, the fruits from the transgenic plants showed to have characteristic similar to that of non-transgenic.
Molecular and phenotypic analysis of elite events of genetically modified Citrus sinensis under field conditions
Keywords: Citros; Plantas transgênicas; Características agronômicas; Resistência a patógenos; Citrus; Transgenic plants; Agronomic characteristics; Resistance to pathogens; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA